2019
DOI: 10.2337/db19-562-p
|View full text |Cite
|
Sign up to set email alerts
|

562-P: The Effect of Vitamin D Supplementation on the Cytokines Levels in Patients with Type 2 Diabetes Mellitus and Diabetic Neuropathy

Abstract: Background: Inflammation plays an important role in the pathogenesis of diabetic neuropathy (DN) in patients with type 2 diabetes (DM2). It seems that vitamin D ((VitD) could be involved in this process, however, the relationship between VitD status and inflammatory markers has not been wildly studied. Hypothesis: The aim was to study the association between VitD status and inflammatory markers in patients with DM2 and DN. Methods: The single-centre randomized study included 62 su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The final column details reported statistical effect of Vitamin D at lowering IL-6 level. Reference Location Condition Age (yrs] N Duration (wks] D3 Dose (IU/day) Outcome Bueloni-Dias [39] Brazil Healthy Women 57 ± 7 160 39 1000 p < 0.05 Costenbader [40] Boston Healthy Older Adults 65 ± 8 1561 52 2000 p > 0.05 Duggan [41] Seattle Overweight Women 62 ± 12 218 52 2000 p = 0.004 Goncalves-Mendes [42] France Healthy Older Adults 71 ± 6 38 13 6667 p = 0.046 Hashemi [43] Iran Multiple Sclerosis 30 ± 9 75 8 7143 p < 0.001 Hashemi [44] Iran Multiple Sclerosis 30 ± 10 75 8 7143 p < 0.001 Miroliaee [45] Iran Ventilator Pneumonia 56 ± 20 46 Single 300,000 p = 0.01 Reid [46] St Louis Asthma 40 ± 13 100 12 4000 p > 0.05 Stepanova [47] Russia Type 2 Diabetes Not Stated 62 …”
Section: Resultsmentioning
confidence: 99%
“…The final column details reported statistical effect of Vitamin D at lowering IL-6 level. Reference Location Condition Age (yrs] N Duration (wks] D3 Dose (IU/day) Outcome Bueloni-Dias [39] Brazil Healthy Women 57 ± 7 160 39 1000 p < 0.05 Costenbader [40] Boston Healthy Older Adults 65 ± 8 1561 52 2000 p > 0.05 Duggan [41] Seattle Overweight Women 62 ± 12 218 52 2000 p = 0.004 Goncalves-Mendes [42] France Healthy Older Adults 71 ± 6 38 13 6667 p = 0.046 Hashemi [43] Iran Multiple Sclerosis 30 ± 9 75 8 7143 p < 0.001 Hashemi [44] Iran Multiple Sclerosis 30 ± 10 75 8 7143 p < 0.001 Miroliaee [45] Iran Ventilator Pneumonia 56 ± 20 46 Single 300,000 p = 0.01 Reid [46] St Louis Asthma 40 ± 13 100 12 4000 p > 0.05 Stepanova [47] Russia Type 2 Diabetes Not Stated 62 …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, previous studies disclosed that vitamin D might prevent the production of IL-6 [45][46][47] and thus could assist in reducing the incidence of type 2 diabetes mellitus [48]. Stepanova et al [49] concluded in their recent single-center randomized trial that the group receiving 40,000 IU cholecalciferol per week for a period of six months showed an improvement in serum IL-6 (p = 0.017). Unfortunately, within this analysis, vitamin D treatment did not support this hypothesis, since the changes observed in IL-6 concentrations were not significant in our T2DM subjects.…”
Section: Discussionmentioning
confidence: 99%